Association between short stature and behavioral and emotional difficulties among children in Jordan: a cross-sectional study - Tamara Kufoof; Randa K. Saad; Redab Al-Ghawanmeh; Seri Sawaqed; Zaid Hamdan; Zaid Qolaghasi; Adnan Alswiti; Layan Sharkas; Osama Sharkas (Frontiers in Endocrinology)
BackgroundShort stature is associated with psychological and emotional challenges, yet its impact on children’s behavioral well-being in Jordan remains underexplored. This study examines the association between short stature and behavioral and emotional difficulties in Jordanian children.MethodsA cross-sectional study was conducted at Prince Hamza Hospital, Amman (2023–2024). We recruited eighty-three children aged 4–14 years with a height percentile ≤3%. The Strengths and Difficulties Questionnaire (SDQ) assessed behavioral and emotional difficulties. Differences in SDQ scores by gender, age group, and growth hormone (GH) therapy status were analyzed.ResultsThe mean total difficulties score was 13.7 ± 6.1, with 30.1% of participants classified in the “high” or “very high” category. Emotional difficulties (31.3%), peer problems (31.3%), and conduct issues (34.9%) were notably prevalent. Boys exhibited significantly higher conduct problems (p < 0.001), hyperactivity (p = 0.002), and total difficulties scores (p = 0.010), while girls showed stronger prosocial behaviors (p = 0.004). No significant differences were observed between younger (3–10 years) and older (11–14 years) children. Children receiving GH therapy reported significantly higher emotional problems (p = 0.029), though other SDQ scores did not differ significantly between treated and untreated groups.ConclusionShort stature in Jordanian children is associated with significant behavioral and emotional challenges, particularly among boys. GH therapy was not associated with improved scores in this sample. A multidisciplinary approach integrating psychological support and public health initiatives is needed to address stigma and improve well-being.